Analisis Kadar Timbal (Pb) pada Air Sumur Gali di Sekitar Bekas Tempat Pembuangan Akhir (TPA) Sampah Punggolaka Kota Kendari - Siti Rabbani Karimuna (Jurnal Kendari Kesehatan Masyarakat, 2025)
The impact of lead (Pb) damages various organs of the human body, especially the nervous system, blood formation system, reproductive system, heart and kidney system and can cause anemia. The former Landfill has certainly hoarded various types of waste, one of which is heavy metals including lead. Lead (Pb) is one of the heavy metals that is toxic to humans The former Punggolaka Landfill (TPA) is a landfill that used to use an open dumping system in its waste management techniques. This can affect the quality of the surrounding groundwater, it is known that the community around the landfill still uses dug well water as a source of clean water for daily needs. This study aims to determine the level of lead (Pb) content in community dug wells located around the former Punggolaka Waste Landfill (TPA) in Kendari City. This study used an observational descriptive method with a sampling technique using total sampling. The results of this study showed that the 5 dug wells that were sampled met the requirements based on quality standards and the quality of the physical condition of the dug wells from 5 wells, there were 3 dug wells that did not meet the requirements. The results of the study can be concluded that the water quality of the dug wells in terms of lead levels (Pb) is all qualified and in terms of the quality of the physical condition of the dug wells, most of them are not qualified